Catching the next wave of recombinant RyR2 cryo-EM structures. Commentary on "Molecular basis for gating of cardiac ryanodine receptor explains the mechanisms for gain- and loss-of function mutations". (July 2022) - Miotto, Marco C.; Marks, Andrew R.
Graphical abstract: Image, graphical abstract